In Vivo Photoactivation of Caged-Thrombin - Arroyo, Jorge G; Jones, Paul B; Porter, Ned A; Hatchell, Diane L (Thrombosis and Haemostasis, 1997)
Aberrant ocular neovascularization is a major cause of blindness in the world. Abnormal blood vessels in the eye may produce corneal opacification, corneal transplant rejection, neovascular glaucoma, vitreous hemorrhage, traction retinal detachment, and subretinal scars from choroidal neovascular membranes (1-5). Light-induced clotting of blood within these abnormal vessels could provide a novel method for the ablation of deleterious neovascularization. Thrombin is a serine proteinase that participates in the final stages of the coagulation cascade. An inhibitor of thrombin, p-Amidinophenyl-(E)-4-diethyl- amino-2-hydroxy-α-methylcinnamate hydrochloride, MeCINN (1), covalently attaches to the active site serine hydroxyl, inhibiting or caging, the enzyme. Photolysis of the caged-thrombin in vitro causes a trans-cis isomerization of MeCINN which leads to regeneration of active enzyme and cleaving of fibrinogen into fibrin (6). Using a rabbit model of corneal neovascularization, we found that light at 366 nm safely and effectively photoactivates intravenous caged-thrombin and produces localized thrombosis in vivo. These results suggest that intra- vascular photoactivation of caged-thrombin could be used to occlude abnormal blood vessels in the human eye.